2022
DOI: 10.3390/nu14224832
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Lactobacillus plantarum (TCI227) Prevented Potassium-Oxonate-Induced Hyperuricemia in Rats

Abstract: Hyperuricemia (HC) is one of the important risk factors for gout, arteriosclerosis, and cardiovascular disease. Animal studies have shown that Lactobacillus plantarum can improve microbiota and immune regulation, as well as inhibit uric acid production. However, it is not clear whether L. plantarum can improve HC and intestinal microbiota. We used potassium oxonate (PO) to induce HC in male SD rats and then treated them with L. plantarum TCI227 in a dose-dependent manner (HC + LD, HC + MD, HC + HD) for 4 weeks… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The animal procedure con rmed the anti-hyperuricemic capability of the strain. The serum UA in mice could be decreased by 35.5% and close to the normal level with the treatment of X7022, and the UA reduction is higher than that of L. plantarum TCI227 (about 23%) [25], similar to that L. plantarum KGM3 (39%) at the dose of 2 × 10 9 CFU/kg [24]. Besides, the strain could reduce BUN and creatinine during the lowering UA in hyperuricemic mice.…”
Section: Discussionmentioning
confidence: 77%
“…The animal procedure con rmed the anti-hyperuricemic capability of the strain. The serum UA in mice could be decreased by 35.5% and close to the normal level with the treatment of X7022, and the UA reduction is higher than that of L. plantarum TCI227 (about 23%) [25], similar to that L. plantarum KGM3 (39%) at the dose of 2 × 10 9 CFU/kg [24]. Besides, the strain could reduce BUN and creatinine during the lowering UA in hyperuricemic mice.…”
Section: Discussionmentioning
confidence: 77%
“…L. plantarum TCI227 can reduce uric acid levels and regulate the composition of intestinal flora, which increased Lactobacillaceae and decreased Deferribacteres and Prevotellaceae . The reduction of uric acid levels by L. plantarum TCI227 may be related to the regulation of gut microbiota [52]. Yamanaka et al [53] found that yoghurt with Lactobacillus PA-3 could improve uric acid levels in healthy people, patients with hyperuricemia and gout, and further found that probiotics rich in yoghurt played a vital role in regulating blood uric acid.…”
Section: New Proposals For Gout Therapymentioning
confidence: 99%
“…The timing and method of intervention for HUA remain controversial, and their application is limited due to drug side effects (Chales 2019;Chien et al 2022;Mehmood et al 2019;Petreski et al 2020). As safer alternatives, probiotics hold great potential for preventing and treating hyperuricemia.…”
Section: Introductionmentioning
confidence: 99%